Economic burden of malaria in Burundian children: An evidence for disease management in resource limited settings - Hezagira, Nina; Youngkong, Sitaporn; Riewpaiboon, Arthorn (Life Sciences, Medicine and Biomedicine, 2022)
In Burundi, malaria is the leading cause of morbidity and mortality, especially in children under five. This results in high clinical burden of the disease; however, its economic burden remains unknown. The aim of this study was to estimate the economic burden associated with malaria in Burundi and explore the factors that can affect the costs. This study was a prospective incidence-based cost-of-illness study analysed from the societal perspective. The study included children aged under five years with malaria infection, who visited and received treatment at any of the two study health facilities in the period of November to December 2019. Data collection was done by reviewing medical and financial records and by interviewing caregivers of the patients. Micro-costing approach was used to estimate the economic costs of malaria per episode. The cost was presented in international dollars (Int) for the year 2019. Stepwise multiple linear regression method was applied to examine the factors affecting the costs and to generate a cost model. Eighty-five children with the average age of 29 months were included in the study. Most of them (70.5%) were treated as in-patient. The out-patient visits costed Int23.5, while the in-patient hospitalization costed Int218.2. The types of medical services, health facilities, antimalarials used, and duration of fever before seeking appropriate medical care were found to affect the costs. The model indicates that up to Int18.76 can be saved per malaria episode if treated early (in less than 2 days). This can save up to Int24,257,748 per year at national level. This study demonstrated that malaria is associated with a considerable economic burden in Burundi. It will support decision makers in deciding an appropriate clinical management for malaria prevention like the community case management program.